Managing Two Fits of Strategic Human Resource Management - Baird, Lloyd; Meshoulam, Ilan (Academy of Management Review, 1988)
A model for developing and implementing human resource management strategies incorporating both an external fit (human resource management fits the developmental stage of the organization) and an internal fit (the components of human resource management complement and support each other) is proposed. Human resource management is seen as having five developmental stages and six strategic components. These are combined to form the Human Resource Strategic Matrix. The implications of these ideas for research and practice are discussed.